(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective: To assess knowledge, awareness and attitude among hospital physicians from Kosovo toward current situation of Health Care System (HCS) especially Secondary Health Care (SHC) in Kosovo. Methods: In this cross-sectional study, anonymous questionnaire were delivered to three regional hospitals in Kosovo. The main outcome measures were physician’s awareness of the management of secondary health care institutions, awareness and use of new technology for improving health care in second level and their suggestions for further improvement. Results: Results are divided into three main categories: I. Relevant information on the knowledge of the health care system, were respondents had valuable information and insight; II. Relevant information on suggested improvements, in which respondents gave their proposals regarding workplace and inter managerial relations and III. Relevant information on continues education possibilities for medical staff. Conclusions: In conclusion there is a need to prioritize proper cooperation between primary, secondary, and third level of health institutions, in terms of entire health management in order to increase the quality of health services delivery, in line with western standards. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.288-293